The Community Network Game Project: Enriching Online Gamers Experience with User Generated Content - Christos Bouras; Andreas Papazois; George Tsichritzis; S Ahmad; R Hamzaoui; E Perelman; A Sahni; G Simon (CONTENT 2010: The Second International Conference on Creative Content Technologies, Lisbon, Portugal, 2010)
One of the most attractive features of Massively Multiplayer Online Games (MMOGs) is the possibility for users to interact with a large number of other users in a variety of collaborative and competitive situations. Gamers within an MMOG typically become members of active communities with mutual interests, shared adventures, and common objectives. We present the EU funded Community Network Game (CNG) project. The CNG project will provide tools to enhance col- laborative activities between online gamers and will develop new tools for the generation, distribution and insertion of user generated content (UGC) into existing MMOGs. CNG will allow the addition of new engaging community services without changing the game code and without adding new processing or network loads to the MMOG central servers. The UGC considered by the CNG project includes 3D objects and graphics as well as video to be shared using peer-to-peer (P2P) technology. We describe the concept, innovations, and objectives of the project.